2020
DOI: 10.2151/sola.2020-013
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Future Climate Projections of Surface Solar Radiation in Japan

Abstract: The ensemble average projections of the Coupled Model Inter-comparison Project Phase 5 (CMIP5) ensemble show future increases in shortwave radiation at the surface (SW) in Japan. We reveal that the Arctic Oscillation-like atmospheric circulation trends cause cloud cover decreases around Japan, leading to increases in the SW. In many cases, impact assessment studies use the outputs of only a few models due to limited research resources. We find that the four climate models used in the Japanese multisector impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…In general, the high-resolution MRI simulations indicated that the topographic pattern of the region would determine the extent of future changes and that, among the investigated variables, these variations remained coherent. Overall, the general patterns agreed with those of previous studies based on ensemble CMIP5 models showing future increases in solar radiation due to circulation trends causing cloud cover decreases and reduced wind speeds around Japan 35 .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In general, the high-resolution MRI simulations indicated that the topographic pattern of the region would determine the extent of future changes and that, among the investigated variables, these variations remained coherent. Overall, the general patterns agreed with those of previous studies based on ensemble CMIP5 models showing future increases in solar radiation due to circulation trends causing cloud cover decreases and reduced wind speeds around Japan 35 .…”
Section: Resultssupporting
confidence: 88%
“…Overall, our analysis of PV power outputs confirmed the results of previous studies that suggested generally increased solar power output in Japan 22 , 35 . Therefore, our results confirm the reliability of the CNN method for producing super-resolution climate scenarios and will enable energy planners to anticipate the effects of future weather variability.…”
Section: Discussionsupporting
confidence: 90%
“…A significant decreasing trend in cloud cover was projected by the end of the 21st century in eastern China (Yang et al., 2018; Zou et al., 2019). Meanwhile, over China as a whole, cloud cover was projected to increase in the future period compared with the past (Dutta et al., 2022; Yu et al., 2019), while other studies have shown opposite changes (Feron et al., 2021; Shiogama et al., 2020). Thus, it is vital to select optimal CMIP6 models and make reliable future projections of winter cloud cover and CDs in China.…”
Section: Introductionmentioning
confidence: 99%
“…Another coordinated multi-sector impact assessment project in Japan called S-8 also used only four CMIP5 GCMs (Hanasaki et al 2014. Shiogama et al (2020 suggested that the selected GCMs of S-8 do not cover the CMIP5 range of shortwave radiation changes in Japan. Shi2020 also developed a method to select a better subset of GCMs that are more widely distributed and are not biased regarding shortwave radiation.…”
Section: Introductionmentioning
confidence: 99%